1989
DOI: 10.1159/000150098
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Homologies among the Genomes of Several Actinophages of <i>Faenia</i> and <i>Saccharopolyspora</i> as Determined by DNA Hybridization

Abstract: The DNA of φFR114, a temperate phage of the thermophilic actinomycete Faenia rectivirgula, was hybridized with the genomes of 11 different phages of Faenia and Saccharopolyspora. This revealed several regions (modules) within the φFR114 DNA which were distributed independently among the genomes of the other phages. The genome of the lytic phage 121, originally described for Sap. erythraea, exhibited a similar modular organization. So far no functions of the possible modules are known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The (pSa phages may be distantly related to the (pFR phages of Faenia and Saccharopolyspora [II], as suggested by homology studies: when <pSaGl DNA was used as a biotinylated probe under low-stringency conditions, three small areas of weak but distinct homology could be mapped on the <pFRI 14 restriction map, indicating some DNA areas (modules) common to both groups of phages [12]. Furthermore, transfec tion experiments with the DNA of (pSaGI showed that its genome can be expressed in Faenia reclivirgula once it has overcome the barrier of the bacterial cell envelope [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The (pSa phages may be distantly related to the (pFR phages of Faenia and Saccharopolyspora [II], as suggested by homology studies: when <pSaGl DNA was used as a biotinylated probe under low-stringency conditions, three small areas of weak but distinct homology could be mapped on the <pFRI 14 restriction map, indicating some DNA areas (modules) common to both groups of phages [12]. Furthermore, transfec tion experiments with the DNA of (pSaGI showed that its genome can be expressed in Faenia reclivirgula once it has overcome the barrier of the bacterial cell envelope [23].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, however, single fragments could be detected which hybridized only very weakly. This could be explained either by short deletions within the phage genome used as a probe or by areas of no or reduced homology between the two phages concerned [12]. However, since no restriction maps of the Saccharomonospora phages have been set up, a deci sion could not be made.…”
Section: Phage Genomesmentioning
confidence: 99%
“…Similarly, common modules constitute a source of error in dotblot hybridizations. Morphologically distinct phages with common modules have been found in coryneform bacteria, Pseudomonas, and streptomycetes [5,8,13,46,47,51]. They doubtless occur elsewhere.…”
Section: Partial Genomic Relationshipsmentioning
confidence: 99%
“…Isolation, restriction analysis and hybridization of DNA with biotinylated probes were carried out as described by Schneider & Kutzner (1989a) and Sonnen et al (1990). Mapping of DNA homology by hybridization was performed according to Schneider & Kutzner (1989b). Hybridizations were carried out in 6 x SSC (1 x SSC is 0.15 M-NaCI, 0.015 ~l-trisodium citrate, pH 7.0) at 60 °C; washing conditions for the determination of hybridization stringency (Meinkoth & Wahl, 1984) were 0.2 x SSC, 60 °C for mediumstringency (homology > 80~) and 0.05 x SSC, 60 °C for high stringency (homology >90~).…”
Section: Methodsmentioning
confidence: 99%